Sewn boats in the Qatar Museums collection, Doha: baggāras and kettuvallams as records of a western Indian Ocean technological tradition. (17th September 2020) - Cooper, John P.; Ghidoni, Alessandro; Zazzaro, Chiara; Ombrato, Luigi
Abstract: Vernacular sewn boats from southern Iran and Kerala, India, in the collection of Qatar Museums are documented and their construction described. The Iranian baggāra s are unique preservations of sewn boats from the Arabian‐Persian Gulf, notable for their previously undocumented keel‐garboard sewing technique and extensive use of bitumen coatings. Comparison between individual boats enables conclusions to be drawn about the builders' conception, as well as variation within the type. The Keralite kettuvallam s represent an ongoing vernacular tradition that is nevertheless poorly documented or preserved in museum contexts. Construction drawings, naval‐lines drawings, and 3D photogrammetry models are provided for all vessels. Resumen: Barcos cosidos en la colección de Museos de Qatar en Doha: baggāras y kettuvallams como registros de la una tradición tecnológica del del Océano Índico Occidental Este artículo documenta y describe la construcción de las embarcaciones cosidas vernáculas del sur de Irán y Kerala, India, en la colección de los Museos de Qatar. Las baggāras iraníes son preservaciones únicas de embarcaciones cosidas del Golfo Arábigo‐Pérsico. Son notables por la técnica de cosido de las tracas de aparadura a la quilla y el uso extendido de recubrimiento de bitumen que previamente no habían sido documentados. La comparación de embarcaciones individuales permite llegar a conclusiones sobre la concepción de los constructores sobre los barcos, así como sobre la variación dentro del tipo. Las kettuvallams keralitas representan una tradición vernácula aún existente que sin embargo ha sido escasamente documentada o preservada en contextos museográficos. El artículo incluye dibujos de construcción, planos de líneas y modelos fotogramétricos 3D de todas las embarcaciones. Palabras clave: Dhow, baggāra, kettuvallam, barcos cosidos, Qatar, India, Kerala, Océano Índico 抽象: 卡塔尔博物馆 (多哈) 藏品中的缝制船:记录西印度洋技术传统的巴加拉和克图瓦拉姆 卡塔尔博物馆对来自伊朗南部和印度喀拉拉邦的土著缝制船藏品登记造册并对其建造方法进行了描述。伊朗的巴加拉船是阿拉伯——波斯湾唯一保存下来的缝制船, 特别是未见于记载的龙骨——龙骨翼板的缝制技术以及沥青涂层的广泛应用。通过对不同船只的比较可导出造船者的建造构想及得出同船型内存在个体差异的结论。喀拉拉的克图瓦拉姆代表了一种持续的土著传统, 但其却缺乏记录, 也很少被博物馆收藏。我们为所有馆藏船只制作了结构图、型线图和3D摄影测量模型。 关键词: 阿拉伯三角帆船, 巴加拉, 克图瓦拉姆, 缝制船, 卡塔尔, 印度, 喀拉拉邦, 印度洋 卡塔爾博物館 (多哈) 藏品中的縫制船:記錄西印度洋技術傳統的巴加拉和克圖瓦拉姆 卡塔爾博物館對來自伊朗南部和印度喀拉拉邦的土著縫制船藏品登記造冊並對其建造方法進行了描述。伊朗的巴加拉船是阿拉伯——波斯灣唯一保存下來的縫制船, 特別是未見于記載的龍骨——龍骨翼板的縫制技術以及瀝青塗層的廣泛應用。通過對不同船只的比較可導出造船者的建造構想及得出同船型內存在個體差異的結論。喀拉拉的克圖瓦拉姆代表了一種持續的土著傳統, 但其卻缺乏記錄, 也很少被博物館收藏。我們爲所有館藏船只制作了結構圖、型線圖和3D攝影測量模型。 關鍵詞: 阿拉伯三角帆船, 巴加拉, 克圖瓦拉姆, 縫制船, 卡塔爾, 印度, 喀拉拉邦, 印度洋 ملخص: